PHARMACOLOGICAL ACTIVITIES OF ‘CHANDRAKHYA’ LEAVES (International Journal of Pharmaceutical Sciences and Drug Research, 2009)
A simple, precise and reproducible reverse phase, isocratic high performance liquid chromatographic method was developed and validated for the quantitative determination of sodium valproate in bulk and enteric coated tablet dosage form. The quantification was carried out using a Nova-pack phenyl, 4µm, 150 mm × 3.9 mm i.d. column, with a mobile phase consisting of acetonitrile: buffer (30:70, v/v) (pH 2.5) at a flow rate of 1.2 ml/min and UV detection at 210 nm. The method was validated for specificity, linearity, accuracy, precision, limit of detection, limit of quantification, robustness and solution stability. The linearity of the proposed method was investigated in the range of 50-1500 µg/ml (r = 0.9999). Mean inter- and intra-assay relative standard deviations (RSD) were less than 2.0 %. The proposed method was successfully applied for the analysis of sodium valproate in bulk and pharmaceutical dosage forms. Also, the method was extended for determination of sodium valproate release from in-vitro dissolution studies.